Chloramphenicol Induces Autophagy and Inhibits the Hypoxia Inducible Factor-1 Alpha Pathway in Non-Small Cell Lung Cancer Cells - Hsu, Han-Lin; Liao, Po-Lin; Cheng, Yu-Wen; Huang, Shih-Hsuan; Wu, Chien-Hua; Li, Ching-Hao; Kang, Jaw-Jou (International journal of molecular sciences, 2019)
Chloramphenicol is an inexpensive and excellent bactericidal antibiotic. It is used to combat anaerobic infections in the Third World countries, whereas its systemic application has been abandoned in developed countries. However, in recent years, clinicians have reintroduced chloramphenicol in clinical practice. In this study, chloramphenicol was found to repress the oxygen-labile transcription factor, hypoxia inducible factor-1 alpha (HIF-1α), in hypoxic A549 and H1299 cells. Furthermore, it suppressed the mRNA levels of vascular endothelial growth factor (VEGF) and glucose transporter 1, eventually decreasing VEGF release. Chloramphenicol initiated the autophagy pathway in treated cells, as observed by the increase in formation of Atg12-Atg5 conjugates, and in beclin-1 and LC3-II levels. The chloramphenicol-mediated HIF-1α degradation was completely reverted by autophagic flux blockage. In HIF-1α-overexpressing cells, the formation of HIF-1α/SENP-1 (Sentrin/SUMO-specific protease 1) protein complex seemed to facilitate the escape of HIF-1α from degradation. Chloramphenicol inhibited HIF-1α/SENP-1 protein interaction, thereby destabilizing HIF-1α protein. The enhancement in HIF-1α degradation due to chloramphenicol was evident during the incubation of the antibiotic before hypoxia and after HIF-1α accumulation. Since HIF-1α plays multiple roles in infections, inflammation, and cancer cell stemness, our findings suggest a potential clinical value of chloramphenicol in the treatment of these conditions.